The future of commercial banking - Candilis, Wray O.; Sparkman, John. (New York : Praeger, 1975)
The historical development of banking structure and the changes that are currently taking place at a very rapid rate are analyzed in the first chapter of this volume.
Including bibliographical references and index.
osa 24/01/2019
Loans
Keywords: Banks and banking